The Asian Developmental State: Reexaminations and New Departures - Chu, Yin-wah (Palgrave Macmillan US, 2016)
This volume re-examines the concept of the developmental state by providing further theoretical specifications, undertaking critical appraisal and theoretical re-interpretation, assessing its value for the emerging economies of China and India, and considering its applicability to South Korea and Taiwan
Keywords: Demokratisierung; Industrialisierung; Wirtschaftswachstum; Entwicklungsländer; Asien; Ost-West-Konflikt; Südosteuropa; Balkanhalbinsel